Conflict or convergence? : Interpreters' and police officers' perceptions of the role of the public service interpreter - Kredens, Krzysztof (Language and Law / Linguagem e Direito, 2017)
This paper presents the ndings of a research project investigating perceptions of public service interpreting among police ocers and practising interpreters in the legal system of England and Wales. The data were secured from both groups responding to six instances of interpreting practice where the interpreter involved had to make an ethics-related choice. The results suggest that despite the markedly dierent professional cultures there are in fact few points of actual professional conict, with the police ocers showing an understanding of the interpreters’ agenda. It is argued this is because both groups ultimately pursue the same aim, namely eective communication.